Campus stylebook a guide to writing & editing for popular publications - Maslog, Crispin Chio editor ([College, Laguna] University of the Philippines, Los Baños, 1990)
A compilation of general rules for writing and editing campus publications. The material is presented to aid both beginning and experienced writers. Additional chapters about Science writing, Writing about Women, and English for Journalists are included as reprints from "Depth news Stylebook", "Press Forum" and "The Manila Times Journalism Handbook.
Fi-16849g donated by Prof. Mamoru Tsuda, MA, UP 1977.
Keywords: Journalism -- Philippines -- Handbooks, manuals, etc; Journalism -- Style manuals; Journalism, College -- Philippines -- Handbooks, manuals, etc